PENGARUH KARAKTERISTIK KEWIRAUSAHAAN, MODAL USAHA DAN PERAN BUSINESS DEVELOPMENT SERVICE TERHADAP PENGEMBANGAN USAHA (STUDI PADA SENTRA INDUSTRI KERUPUK DESA KEDUNGREJO SIDOARJO JAWA TIMUR) - Putri, Kartika; Pradhanawati, Ari; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
This study aims to determine whether there is influence between the characteristics of entrepreneurship, venture capital and the role of Business Development Services to business development. Type of study is Exploratif Research. Data collection methods used are literature studies, questionnaires, interviews and observations. Of the 33 total of study population, retrieved a sample of 33 respondents to the census method. Analysis of data using the correlation coefficient, coefficient of determination, regression analysis, and t test and f test to prove the hypothesis by using SPSS 16.0.The results of the study through the analysis of the coefficient of determination shows that the characteristics of entrepreneurship, business capital, and the role of Business Development Service has a positive and significant impact on business development partially (with the results of respectively 29.5%, 45.7%, and 38.7 %) and 48.7% simultans to the development effort.